(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: The Kenya population and housing census (2019) ranked Homabay County among the 15 counties with the highest maternal mortality rate (MMR) of 516 deaths in 100,000 livebirths and neonatal mortality rate (NMR) of 26 in 1,000 livebirths. Baseline assessment reported gaps including dysfunctional maternal and perinatal death surveillance and response system, and untimely perinatal deaths audited. Other challenges contributing to near misses and mortality include erratic availability of blood/blood products, staff shortages affecting the offering of CEmONC services, interfacility referral challenges, not exploiting partnerships with private and faith-based health facilities in the county, and HCW knowledge and skills deficit, especially in management of common causes of death, such as postpartum hemorrhage and eclampsia Methods: MCGL’s objective was to work with the County’s leadership to revitalize the MPDSR system and work toward responding to the causes and avoidable factors contributing to the high burden of maternal and perinatal deaths in the County. MCGL trained HCWs on harvesting and handling of blood products, management of PPH and eclampsia, development of county referral strategy, linkage to private and faith-based HFs, capabilities, support weekly MPDSR committee meetings, develop, and roll out MPDSR of weekly monitoring tool, formation of QI teams, and support for social accountability activities. Results: Improved implementation of MPDSR action points included increased number of CEmONC health facilities, availability and access to blood during PPH emergencies, and point-of-care ultrasound machines in 13 health facilities. There was notable improvement of timely perinatal deaths of audits 47% (70/152). Conclusions: Deliberate and collective effort by the leadership with close follow-up can improve timely auditing and response , which improves the quality of care for mothers and newborns receiving HFs.